Association between the SMN2 gene copy number and clinical characteristics of patients with spinal muscular atrophy with homozygous deletion of exon 7 of the SMN1 gene - Žarkov Marija; Stojadinović Aleksandra; Sekulić Slobodan; Barjaktarović Iva; Stojiljković Olivera; Perić Stojan; Keković Goran; Drašković Biljana; Stević Zorica (Vojnosanitetski Pregled)
Background/Aim. Spinal muscular atrophy (SMA) is an autosomal recessive disease characterized by degeneration of alpha motor neurons in the spinal cord and the medulla oblongata, causing progressive muscle weakness and atrophy. The aim of this study was to determine association between the SMN2 gene copy number and disease phenotype in Serbian patients with SMA with homozygous deletion of exon 7 of the SMN1 gene. Methods. The patients were identified using regional Serbian hospital databases. Investigated clinical characteristics of the disease were: patients’ gender, age at disease onset, achieved and current developmental milestones, disease duration, current age, and the presence of the spinal deformities and joint contractures. The number of SMN1 and SMN2 gene copies was determined using real-time polymerase chain reaction (PCR). Results. Among 43 identified patients, 37 (86.0%) showed homozygous deletion of SMN1 exon 7. One (2.7%) of 37 patients had SMA type I with 3 SMN2 copies, 11 (29.7%) patients had SMA type II with 3.1 ± 0.7 copies, 17 (45.9%) patients had SMA type III with 3.7 ± 0.9 copies, while 8 (21.6%) patients had SMA type IV with 4.2 ± 0.9 copies. There was a progressive increase in the SMN2 gene copy number from type II towards type IV (p < 0.05). A higher SMN2 gene copy number was associated with better current motor performance (p < 0.05). Conclusion. In the Serbian patients with SMA, a higher SMN2 gene copy number correlated with less severe disease phenotype. A possible effect of other phenotype modifiers should not be neglected.